2021
DOI: 10.3389/fonc.2021.768758
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Magnetic Fields Inhibit Mitochondrial Respiration, Promote Oxidative Stress and Produce Loss of Mitochondrial Integrity in Cancer Cells

Abstract: Electromagnetic fields (EMF) raise intracellular levels of reactive oxygen species (ROS) that can be toxic to cancer cells. Because weak magnetic fields influence spin state pairing in redox-active radical electron pairs, we hypothesize that they disrupt electron flow in the mitochondrial electron transport chain (ETC). We tested this hypothesis by studying the effects of oscillating magnetic fields (sOMF) produced by a new noninvasive device involving permanent magnets spinning with specific frequency and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…As shown by Hong et al (1995), the effects of such magnetic induction concentrate on the cellular walls/membranes, due to the shielding effect mostly 53 . Such a statement is coherent not only with the data presented in the current work (showing disturbances in the bacterial cell walls as a result of the RMF exposure) but also with the results shown recently by Sharpe et al (2021), who reported the damage of mitochondrial membranes in cancer cells exposed to the RMF 54 . It should be underlined that process of biofilm matrix formation is facilitated to a major extent by specialized protein systems localized throughout the bacterial cell walls and membranes 55 .…”
Section: Discussionsupporting
confidence: 93%
“…As shown by Hong et al (1995), the effects of such magnetic induction concentrate on the cellular walls/membranes, due to the shielding effect mostly 53 . Such a statement is coherent not only with the data presented in the current work (showing disturbances in the bacterial cell walls as a result of the RMF exposure) but also with the results shown recently by Sharpe et al (2021), who reported the damage of mitochondrial membranes in cancer cells exposed to the RMF 54 . It should be underlined that process of biofilm matrix formation is facilitated to a major extent by specialized protein systems localized throughout the bacterial cell walls and membranes 55 .…”
Section: Discussionsupporting
confidence: 93%
“…It is now clear that electromagnetic fields, such as from rotating magnets, can profoundly influence mitochondrial function, for instance, as an approach to kill cancer cells 53 , or at low intensities (10 µT) and low frequency (1–8 Hz) to induce mitophagy and rejuvenate mitochondrial function 54 . Other data also suggest that prolonged EMF can enhance cardiac and osteogenic mitochondrial function—the proposed mechanism involving a mild production of ROS and possibly complex I involvement 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…An important feature has been to eliminate electromagnetic interference from heating or control functions. This is important for the following reasons: (1) electric fields as low as several millivolts per meter have been found to have biological effects on cellular behavior (Yamashita, 2015) and (2) Magnetic fields on the order of several microteslas have been found to affect cell behavior (Sharpe et al, 2021), also through the well-known ion cyclotron resonance (ICR) phenomena. A simple heating element embedded T A B L E 4 Temperature analysis in some components of mini-incubator when electric and magnetic fields are applied for 1 h. around a culture dish can produce a magnetic field comparable to ten microteslas by simple textbook calculations.…”
Section: Discussionmentioning
confidence: 99%